2022
DOI: 10.3390/land11122193
|View full text |Cite
|
Sign up to set email alerts
|

Just Energy Transition: Learning from the Past for a More Just and Sustainable Hydrogen Transition in West Africa

Abstract: The rising demand for energy and the aim of moving away from fossil fuels and to low-carbon power have led many countries to move to alternative sources including solar energy, wind, geothermal energy, biomass, and hydrogen. Hydrogen is often considered a “missing link” in guaranteeing the energy transition, providing storage, and covering the volatility and intermittency of renewable energy generation. However, due to potential injustice with regard to the distribution of risks, benefits, and costs (i.e., in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 101 publications
0
7
0
Order By: Relevance
“…They can be accomplished by clear leadership, effective administration, and the adaptation of business models, expertise, and technologies to the various local conditions. Modern bioenergy has the potential to alter Africa, with societal advantages spreading across many other fields and going far beyond just energy production (Löhr et al, 2022).…”
Section: Future Consideration and Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…They can be accomplished by clear leadership, effective administration, and the adaptation of business models, expertise, and technologies to the various local conditions. Modern bioenergy has the potential to alter Africa, with societal advantages spreading across many other fields and going far beyond just energy production (Löhr et al, 2022).…”
Section: Future Consideration and Conclusionmentioning
confidence: 99%
“…Political pressure to implement plans for utilizing renewable energy is constantly emergent due to Europe's significant import need for fuel and its pledges to lessen CO 2 emissions under the Kyoto Protocol. It is essential to reach the 1.5 °C objective that the electricity industry is decarbonized by 2050 (IRENA, 2022) As a result, Europe hopes to use a lot more biofuels than it presently generates (Löhr et al, 2022).…”
Section: Future Consideration and Conclusionmentioning
confidence: 99%
“…This has led to improved credit rating of the country (albeit at low levels), thereby providing the government somewhat better financing conditions. One additional challenge for Nigeria's energy transition is the lack of skilled workers and expertise of maintenance after project implementation, which is why renewable energy project often fail (Löhr et al, 2022). Despite various programs and initiatives by the Nigerian government to promote solar energy utilization, inadequate planning and longterm government support often lead to implementation issues, such as a missing long-term maintenance.…”
Section: Compensation Payments For Leaving Fossils In the Ground Are ...mentioning
confidence: 99%
“…It underscores the massive need for both energy transition and community benefit sharing, emphasizing that an energy transition requires access to sustainable and affordable energy for all (SDG 7). Löhr et al (2022) summarizes energy policy and highlights that in the Rural Electrification Strategy and Implementation Plan (RESIP), Nigeria aimed for an electrification rate of 75% by 2020, a target they missed. They now aim for 100% electrification by 2040, providing access to 500,000 households per year over a 10-year period -2030Löhr et al, 2022).…”
Section: Figurementioning
confidence: 99%
“…A systematic review of the literature was recently reported, with a focus on the role of end users in the increased uptake of energy transition technologies [8]. Individual clean hydrogen case studies for different countries were also reported in which the authors provided prevalent scenarios and expected outcomes for different regions (Japan [9]; Africa and Europe [10,11]; China [12]; Germany [13]; Russia [14]; Australia [15]; the Global South [16]; Qatar [17]; South America [18]; the Middle East [19]; Mexico [20]; and Canada [21]). A number of review studies were also conducted on challenges and opportunities for innovation in hydrogen-related technologies [22][23][24], with particular focus on production [25][26][27], storage [28][29][30], distribution [31,32], grid integration [33,34], and utilization [35,36].…”
Section: Introductionmentioning
confidence: 99%